Trauma : una etiología infrecuente del pseudoquiste pulmonar (2014)
ABSTRACT: Pulmonary pseudocyst secondary to blunt chest trauma is a rare cavitary lesion in the lung parenchyma that lacks an epithelial lining. It is more common in children and adolescents in whom the chest wall is less rigid. Clinical manifestations are usually benign and resolve spontaneously in two to four months after the trauma. We present the evolution of a child who suffered a closed chest trauma as a pedestrian, after which a cystic lesion appeared in the lung parenchyma, without very obvious symptoms; subsequently the cystic image resolved when he was already asymptomatic.